The J Girls : a Reality Show - Hurt, Rochelle (Blue light books., 2022)
Winner of the 2021 Blue Light Books Prize, Rochelle Hurt's The J Girls: A Reality Show is a tribute to the grit and glitter of millennial girlhood, a testament to its dangers and traumas, and an elegy for adolescent friendships.